Pengaruh Fee Audit, Pengalaman Auditor dan Due Professional Care Pada Kualitas Audit - Sutrisni, Ni Komang; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 21 No 3 (2017)DO - 10.24843/EJA.2017.v21.i03.p09, 2017)
The Company currently requires auditing services (Accountants) quality to help conduct a successful examination of a company. An accountant should pay attention to the quality of the audit, because with a good quality audit is expected to produce financial reports that can be trusted by users of financial information. The results of a good audit quality in the form of transparent financial statements, accountable and in accordance with the applicable SAK, can improve the performance of the company and later the results of financial statements can be seen by stakeholders concerned and reflect the company image in the eyes of society. The purpose of this study is to determine the effect of audit fees, auditor experience and due professional care to audit quality of Public Accountant office in Bali. This research was conducted at Public Accounting Firm (KAP) of Bali Province which has been registered in Indonesian Institute of Certified Public (IAPI) with seven KAP in 2016 with total auditor counted 73 people as sample through saturated sample method. Data was collected by distributing questionnaires to 73 respondents, with 42 respondents returning and 31 not being used because they did not meet the criteria through multiple linear regression analysis technique. Based on the results of the analysis, through the model feasibility test proves that audit fees, auditor experience and due professional care have a positive influence on audit quality at Public Accountant office in Bali. Through t test analysis it is known that audit fees, experience and due professional care has a partial positive effect on audit quality of Public Accountant office in Bali.